SOSIALISASI KEBIJAKAN TENTANG PERLINDUNGAN KONSUMEN OLEH BADAN PENYELESAIAN SENGKETA KONSUMEN TENTANG MAKANAN DAN MINUMAN DI PEKANBARU (IMPLEMENTASI UNDANG-UNDANG NOMOR 8 TAHUN 1999) - Deardo " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Lack of public knowledge about consumer protection as one of the problems of fraud and loss prevention on food and beverage in Pekanbaru City, still a lack of knowledge about consumer protection resulting does not know the procedures for submitting the complaint if harmed . This is because lack of socialization received by the public about consumer protection .The purpose of this study was to know the implementation of policy dissemination of consumer protection by Badan Penyelesaian Sengketa Konsumen About food and beverage in Pekanbaru (Implementation of Undang–Undang number 8 years 1999) on consumers and businesses.The concept of the theory is a of communication used consisting of communicators (those who convey the message), says what (masege delivered), in the which channel (media used in deliver the massege), the communicant (which receives message), the effect (effect posed). This study used qualitive research methods to the assessment of descriptive data. In collecting the data, the research used interview techniques, observation and study of literature, using key informant and the informant as a supplementary source of information.After investigate is done , it was found that socialization has been done by Badan Penyelesaian Sengketa Konsumenis not enough and public participationare still lacking. Many of people who still do not understand and even there are whos till yet to understand about consumer protection and the existence of Badan Penyelesaian Sengketa KonsumenKeyword : Socialization, Policy Dissemination of Consumer Protection, Environment